Tuning the Oxygen Reduction Activity and Stability of Ni(OH)2@Pt/C Catalysts through Controlling Pt Surface Composition, Strain, and Electronic Structure. (1st September 2017) - Godínez-Salomón, Fernando; Rhodes, Christopher P.; Alcantara, K. Suarez; Zhu, Qiushi; Canton, S.E.; Calderon, H.A.; Reyes-Rodríguez, J.L.; Leyva, M.A.; Solorza-Feria, O.
Graphical abstract: Highlights: Electrochemical performance was tuned by changing the Pt surface composition. The strain ratio and electronic properties were controlled by the amount of Pt deposited on the Ni(OH)2 core. Decreasing the percentage of Pt on Ni(OH)2 promoted higher electrocatalytic activity for the ORR, but decreased stability. Abstract: Nanoparticles of Ni(OH)2 surrounded with ultra-low Pt content and supported on functionalized carbon were prepared by a scalable synthesis method and investigated as electrocatalysts for the oxygen reduction reaction (ORR) in acidic media. The effect of altering the Pt surface composition on the Ni(OH)2 nanoparticle core was investigated as a route to simultaneously increase the ORR activity and stability. Modifying the Pt surface composition resulted in both structural and electronic changes. Decreasing the Pt surface composition resulted in stronger Pt-Pt compressive strain and decrease in the occupancy of d-band vacancies per atom. The correlation of strain and d-vacancies with ORR activity and stability showed a Volcano-type tendency, with the 6 wt. % Pt sample showing the highest activity and stability. The electrochemical results obtained using rotating disk electrode (RDE) tests showed an enhancement of about six times higher surface and mass-normalized activity as well as improved durability compared to commercial Pt/C. These improvements were further corroborated by single cell membrane electrode assembly (MEA) tests where similar trends were observed, showing higher power densities with lower Pt loadings, in comparison with commercial Pt/C. These results show that new electrocatalysts with higher activity and stability can be obtained through precise control of the atomic-level catalyst structure.